Implementation of Concurrent Engineering and Analytical Network Process In Manufacturing Process and Material Analysis of Metal Matrix Composites Automotive Component - Fatchurrohman, Nanang; Suraya, Sulaiman; S. M., Sapuan; M. K. A., Ariffin; B. T. H. T., Baharuddin (2014)
This study presents an implementation of concurrent engineering (CE) and analytical network process (ANP) to form a new rating method as part of the manufacturing process and material analysis in product development environment. The proposed procedure is referred as concurrent network (CN). It is planned for CN to carry out simultaneous analysis of all aspects of product elements by using CE strategy. Furthermore, CN enables interdependence and interrelationship analysis between product elements by implementing ANP. In this study, CN is utilized for manufacturing process and material analysis of metal matrix composites (MMCs) automotive component which is the brake disc. The results show that by using CN, all product parameters can be analysed comprehensively and the importance weights of product parameters with regard to MMCs brake disc performance are obtained.